Problematika Implementasi Akad Mudh?rabah pada Perbankan Syariah di Indonesia: Problematika Implementasi Akad Mudh?rabah pada Perbankan Syariah di Indonesia - Rasyid, Moh. (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
This paper examines the implementation of the mudhārabah contract in Islamic banking in Indonesia, explicitly emphasizing the aspects of sharia, fiqh, and the DSN-MUI fatwa as a starting point. The urgency of this paper is in a position not only as constructive criticism of financial institutions that carry out a religious mission but also as a means of discussion for students, academics, and banking practitioners so that sharia banking operations remain on the rails of Islamic law. Because there are still many findings in the field regarding the incompatibility of Islamic banking operations with the provisions of fiqh and the DSN-MUI fatwa regarding mudhārabah, this research is qualitative research with a juridical-normative approach. This study concludes at least two things. First, the mudhārabah formula has evolved from the concept of direct financing to indirect financing. Second, in practice, the provisions of sharia, fiqh, and the DSN-MUI fatwa regarding mudhārabah are not fully implemented as they should be in some sharia banking or financial institutions in Indonesia. The provisions concerning guarantees and the imposition of capital compensation in the mudhārabah contract are the two things that are most susceptible to causing a gap between das sein and das sollen in Islamic banking.